Creativity and Generation of Ideas in the Design of Children's Toys - Bogdan Bucur; Andreea Ban; Sorin Vlase; Arina Modrea (MDPI AG, 2023)
Creativity offers new, interesting, and valuable things that can be intangible (ideas, a theory, songs, etc.) or physical objects (a painting, invention, machine). Creativity implies a lot of qualities of the creator such as imagination, creative work, and innovation and it also improves learning and memory. Many of history's most important discoveries are the results of creative activity. Repetition leads to mastery of a concept through understanding and produces increased self-confidence. Confidence increases the willingness to act on creativity-to explore, discover, and learn. This positive cycle of learning is fueled by the curiosity and enjoyment that comes from discovery and understanding. We are social creatures, so the greatest reward and pleasure comes from the admiration and support received from loved and respected people. Stimulating children's interest through play also defines solving through exploration regarding the accumulation of new essential information for knowing values and other useful information, by stimulating curiosity and creativity as well as discovering new resources that generate creative ideas, allowing the acquisition of practical skills. All these aspects are oriented and define the premises for the harmonious development of children towards a new existential stage. Thus, taking these aspects into account will have future effects on self-confidence, work strategies, school results, as well as the desire to study and the ability to store and organize accumulated information. The approach of the case study presents through the game, a motivational alternative, staged regarding the generation of creative ideas in the development and materialization of the concept. It is well known that during childhood, many things are acquired by children through selective association and depending on the sensory perception of objects, namely preferred colors, functions, and predefined shapes, proportional to the anthropometric dimensions specific to preschool age. The article proposes the creative approach and generation of ideas on the design of children's toys; namely, a case study is presented: children's toy set-teacup.